30-day mortality after coronary artery bypass grafting and valve surgery has greatly improved over the last decade, but the 1-year mortality remains constant - Hansen, Laura Sommer (Ann Card Anaesth, 2015)
INTRODUCTION: European system for cardiac operative risk evaluation (EuroSCORE) is a valuable tool in control of the quality of cardiac surgery. However, the validity of the risk score for the individual patient may be questioned. The present study was carried out to investigate whether the continued fall in short-term mortality reflects an actual improvement in late mortality, and subsequently, to investigate EuroSCORE as predictor of 1-year mortality. METHODS: A population-based cohort study of 25,602 patients from a 12-year period from three public university hospitals undergoing coronary artery bypass grafting (CABG) or valve surgery. Analysis was carried out based on EuroSCORE, age and co-morbidity factors (residual EuroSCORE). RESULTS: During the period the average age increased from 65.1 ± 10.0 years to 68.9 ± 10.7 years (P < 0.001, one-way ANOVA), and the number of females increased from 26.0% to 28.2% (P = 0.0012, Chi-square test). The total EuroSCORE increased from 4.67 to 5.68 while the residual EuroSCORE decreased from 2.64 to 1.83. Thirty-day mortality decreased from 4.07% in 1999–2000 to 2.44% in 2011–2012 (P = 0.0056; Chi-square test), while 1-year mortality was unchanged (6.50% in 1999–2000 vs. 6.25% in 2011–2012 [P = 0.8086; Chi-square test]). DISCUSSION: The study demonstrates that both co-morbidity and age has a great impact on 30-day mortality. However, with time the impact of co-morbidity seems less. Thus, age is more important than co-morbidity in late mortality. The various developments in short and long-term mortality are not readily explained. CONCLUSION: Although 30-day mortality of CABG and valve surgery patients has decreased during the 12-year period, the 1-year mortality remains the same.